Macrophage migration inhibitory factor is involved in antineutrophil cytoplasmic antibody-mediated activation of C5a-primed neutrophils - Jian Hao; Tiegang Lv; Liping Xu; Mao Ran; Kaili Wu (BMC Immunology, 2019)
Abstract Background C5a is important for antineutrophil cytoplasmic antibody (ANCA)-mediated activation of neutrophils. The present study aimed to assess the role of macrophage migration inhibitory factor (MIF) in ANCA-mediated activation of C5a-primed neutrophils. The effects of MIF on ANCA-mediated neutrophil respiratory burst and degranulation were determined. In addition, the effect of a MIF antagonist on the activation of C5a-primed neutrophils was assessed. Results MIF treatment resulted in increased membrane proteinase-3 (mPR3) expression on neutrophils and enhanced myeloperoxidase (MPO) amounts in neutrophil culture supernatants. The concentration of MIF was significantly higher in the neutrophils supernatant primed with C5a (negative control: 14.2 ± 1.16 ng/ml; C5a: 45.8 ± 2.8 ng/ml, P < 0.001 vs. negative control; C5a + IgG: 44.8 ± 1.93 ng/ml, P < 0.001 vs. negative control; C5a + MPO-ANCA: 73.0 ± 5.5 ng/ml, P < 0.001 vs. C5a; and C5a + PR3-ANCA: 69.4 ± 5.35 ng/ml, P < 0.001 vs. C5a). MIF primed neutrophils to undergo respiratory burst and degranulation in response to ANCA. Indeed, mean fluorescence intensity (a measure of respiratory burst) was significantly higher in MIF-primed neutrophils activated with MPO-ANCA-positive IgG or PR3-ANCA-positive IgG compared with non-primed neutrophils. Meanwhile, a MIF antagonist reduced oxygen radical production in C5a-primed neutrophils treated with patient-derived ANCA-positive IgG. Conclusions MIF can prime neutrophils to undergo ANCA-mediated respiratory burst and degranulation. Blocking MIF resulted in reduced ANCA-mediated activation of C5a-primed neutrophils. These findings indicated that the interaction between MIF and C5a may contribute to ANCA-mediated neutrophil activation.